2022
DOI: 10.3389/fneur.2021.646817
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Induces Mitochondrial Autophagy to Prevent Parkinson's Disease in Rats via miR-30b and the SIRT1/AMPK/mTOR Pathway

Abstract: Parkinson's disease (PD) is a prevailing neurodegenerative disorder. Baicalein has neuroprotective effects on PD animals, but its mechanism is not clarified. We explored baicalein effects on PD rats. PD rat models were established by injecting 6-hydroxydopamine into the striatum of substantia nigra on the left side of the rat brain and treated with baicalein. Dopamine (DA) content, neuronal apoptosis, neuronal injury, neuronal mitochondria, and autophagy were assessed. Baicalein-treated PD rats were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Bai works on the SIRT1/ AMPK/mTOR pathway to exert neuroprotective effects in Parkinson's rats. 47 Bai protects against fructose-induced hepatic steatosis in rats by activating the AMPK/PGC-1α and PPARα pathways to promote fatty acid oxidation. 48 According to our results, CPF exposure significantly inhibited the expression of the AMPK/SIRT1/pGC-1α pathway, accompanied by reduced mitochondrial biogenesis and mitochondrial dynamic imbalance, and excessive oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bai works on the SIRT1/ AMPK/mTOR pathway to exert neuroprotective effects in Parkinson's rats. 47 Bai protects against fructose-induced hepatic steatosis in rats by activating the AMPK/PGC-1α and PPARα pathways to promote fatty acid oxidation. 48 According to our results, CPF exposure significantly inhibited the expression of the AMPK/SIRT1/pGC-1α pathway, accompanied by reduced mitochondrial biogenesis and mitochondrial dynamic imbalance, and excessive oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that Bai can act on AMPK and play a beneficial role in a variety of diseases. Bai works on the SIRT1/AMPK/mTOR pathway to exert neuroprotective effects in Parkinson’s rats . Bai protects against fructose-induced hepatic steatosis in rats by activating the AMPK/PGC-1α and PPARα pathways to promote fatty acid oxidation .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that the mTOR signaling pathway is suppressed by miR‐30b‐5p overexpression in LPS‐induced PC12 cells, which was rescued after NEFL upregulation. Overexpression of miR‐30b‐5p has also been reported to partially reverse the inhibitory effect of baicalein on the AMPK/mTOR pathway in Parkinson's disease (Chen et al., 2021 ). The difference from our findings may be explained by the different animal and cell models we used and the influence of other interventions such as baicalein treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein has been shown to exert neuroprotective effects in the substantia nigra of 6-hydroxydopamine-induced Parkinson disease model rats by stimulating mitochondrial autophagy via enhancing the phosphorylation level of AMPK and reducing mTOR [ 127 ].…”
Section: Potential Therapeutic Involvement Of Autophagy In Parkinson ...mentioning
confidence: 99%